2011
DOI: 10.1111/j.1439-0531.2011.01813.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic FGF Promotes Proliferation of Ovarian Granulosa Cells in the Laying Chickens Via FGFR1 and PKC Pathway

Abstract: The proliferating effect of basic fibroblast growth factor (bFGF) on granulosa cells from ovarian pre-hierarchical follicles was evaluated in the laying chickens. Expression of bFGF receptor 1 (FGFR1) from small yellow follicles was determined by immunohistochemistry and RT-PCR. The FGFR1 protein and mRNA were intensively expressed in the granulosa layer. After 8- to 24-h treatment with bFGF (0.1-100 ng/ml), the proliferation of cultured granulosa cells was remarkably enhanced in a dose- and time-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The only study characterizing CCND1 mRNA in bovine GC reported no change during an estrous cycle, while both CCND2 and CCND3 mRNA expression differed among phases of the estrous cycle (Shimizu et al, 2013). However, CCND1 mRNA is induced by GDF9 in human GC (Huang et al, 2009) and by EGF, FGF2 and ginsenosides in chicken GC (Tan et al, 2010; Lin et al, 2011; 2012). In endometrial tissue, FGF9 induces CCND1 (Schwartz et al, 2003; Wing et al, 2005; Chan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The only study characterizing CCND1 mRNA in bovine GC reported no change during an estrous cycle, while both CCND2 and CCND3 mRNA expression differed among phases of the estrous cycle (Shimizu et al, 2013). However, CCND1 mRNA is induced by GDF9 in human GC (Huang et al, 2009) and by EGF, FGF2 and ginsenosides in chicken GC (Tan et al, 2010; Lin et al, 2011; 2012). In endometrial tissue, FGF9 induces CCND1 (Schwartz et al, 2003; Wing et al, 2005; Chan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 signaling induces phosphorylation of tyrosine residues activating protein kinase C (PKC), MAPK, and PI3K pathways through ligand-binding dimerization of FGFR (Dorey & Amaya, 2010). Among the reproductive and embryonic tissues, FGF2 stimulates proliferation of avian granulosa cells of ovary by activation of PKC pathways after binding FGFR1 (Lin, Jia, Zeng, Mi, & Zhang, 2012). In addition, FGF2 activates migration of ovine trophoblast cells through MAPKdependent signal transduction (Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Basic FGF ( bFGF ) plays diverse roles in cell proliferation and differentiation during embryo development. Specifically, in ovarian germ cell development, bFGF accelerates cell proliferation by binding with FGFR1 and maintaining its undifferentiated status (He et al, ; Lin, Jia, Zeng, Mi, & Zhang, ). These two genes, along with NTRK1 , which is discussed above, represent three out of the five membrane receptors in the cell proliferation portion of the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%